PERAN LEMBAGA AMIL ZAKAT WAHDAH INSPIRASI ZAKAT DALAM MENGELOLA ZAKAT KONSUMTIF DI KOTA TENGGARONG - Wiyono, Dimas Andi; Ridho, Miftahur; Mustafa, Muhammad Rojul Kamil (Fakultas Ushuluddin, Adab, dan Dakwah UIN Sultan Aji Muhammad Idris Samarinda, 2023)
This study has a goal, namely the role of Wahdah Inspirasi Zakat (WIZ) in managing consumtive zakat in Tenggarong city. This research has aims to find out the inhibiting and supporting factors for Wahdah Inspirasi Zakat Tenggarong City in managing consumtive zakat. The type of research is descriptive qualitative research. The results of this study indicate that this amil zakat institution carries out two main roles in managing consumtive zakat in Tenggarong City. The first important role is to complement government programs, than the second is to provide a social safety net (JPS) for people who are entitled to receive in Tenggarong City. In this study there were inhibiting and dupporting factors, namely inaccurate data obtained, lack of human resources, and limited media. While the supporting factors was having many sympathizers and still under the auspices of community organizations. Keyword: Zakat, consumption Zakat, Wahdah Inspirasi Zakat